Pengaruhi Kualitas Pelayanan, Fasilitas Dan Ketepatan Waktu Terhadap Kepuasan Pelanggan: Studi Kasus Pada Konsumen Pengguna Jasa Pengiriman Barang (J&T) Di Pandaan - Mirzha Zhulfy Zaintara (Universitas Katolik Widya Karya Malang, 2023)
The purpose of this study was to see the effect of service quality, facilities and timeliness on customer satisfaction at PT. Global Jet Express (J&T) in Pandaan. This study used a quantitative research approach with data collection techniques by distributing questionnaires to 100 consumers. The data analysis method used is Multiple Linear Regression analysis by calculating the SPSS 23 software in which the data will be described, analyzed, and discussed in order to answer and prove the proposed hypothesis. Based on the research results, the Service Quality variable has a significant effect on Customer Satisfaction, the Facilities variable has a significant effect on Customer Satisfactioni and Timeliness has a significant effect on Customer Satisfaction at PT. Global Jet Express (J&T) in Pandaan. While simultaneously the Quality of Service, Facilities and Timeliness have a positive and significant effect on Customer Satisfaction.